Dealing with low amounts of degraded DNA: Evaluation of SNP typing of challenging forensic samples by using massive parallel sequencing. Issue 1 (December 2019) - Turchi, Chiara; Onofri, Valerio; Melchionda, Filomena; Bini, Carla; Previderè, Carlo; Carnevali, Eugenia; Robino, Carlo; Sorçaburu-Ciglieri, Solange; Marrubini, Giorgio; Pelotti, Susi; Fattorini, Paolo; Tagliabracci, Adriano
Abstract: A set of eighty-two forensic samples with different levels of degradation, as well five in vitro damaged samples were analyzed by the Precision ID Identity Panel. PCR amplifications were performed with scalar amount of DNA (from 1 ng to 12 pg) and through different number of cycles. A minimum coverage of 50 x was adopted for "locus call". Very informative profiles (based on about 65–70% of the loci) were obtained even in highly degraded samples when the amount of template range from 0.1 to 1.0 ng. When dealing with low amount of degraded DNAs, no more than half of the loci were typed, and the risk of mistyping (due to drop out phenomena) increased dramatically. The employment of a high number of PCR cycles is discussed.